2015
DOI: 10.1007/s11605-015-2891-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Laparoscopic Versus Open Resection for Transverse Colon Cancer

Abstract: Laparoscopic resection for transverse colon cancer is associated with better short-term outcomes and equivalent long-term oncologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Short-term surgical outcomes including operating time, blood loss, perioperative complications, hospital stay, and re-hospitalization rates were comparable to those published previously (4)(5)(6)(8)(9)(10)(11)(12)14). Table 2 shows the short-term outcomes of laparoscopic transverse cancer resections in eight papers, including the present work.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Short-term surgical outcomes including operating time, blood loss, perioperative complications, hospital stay, and re-hospitalization rates were comparable to those published previously (4)(5)(6)(8)(9)(10)(11)(12)14). Table 2 shows the short-term outcomes of laparoscopic transverse cancer resections in eight papers, including the present work.…”
Section: Discussionsupporting
confidence: 79%
“…Laparoscopic resection for transverse colon cancer is technically challenging because of difficulties caused by anatomical variations and barriers (4-7). There have been a limited number of reports showing its validity and feasibility to date (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Several studies demonstrated the clinical value of 3-D CT angiography for evaluating the vascular anatomy (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decades, several large prospective randomized trials have demonstrated better short-term clinical outcomes of laparoscopic surgery for colorectal cancer, and also established the long-term oncological safety of laparoscopic surgery for colorectal cancer [ 10 11 12 13 14 ]. So nowadays, many surgeons consider laparoscopic surgery as a better surgical option to treat patients suffering from colorectal cancer than conventional open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of living standards and the extension of life expectancy, the incidence of colon cancer is increasingly rising and will continue to rise in China[ 1 , 2 ]. Surgery is the mainstay of treatment for colon cancer.…”
Section: Introductionmentioning
confidence: 99%